SMART GOVENRMET AND ITS APPLICATIONS IN INTELLIGENT TRANSPORTATION: Analytical Study Of The Views Of A Sample Of Employees In Iraqi Organizations - Salman Abood Zbar (Iraqi Journal for Administrative Sciences, 2024)
This study aimed to identify the smart government and its applications in intelligent transport and its impact on the variables of the operational efficiency of the transport system ( Increase the operational efficiency variables of the transport system , improvement the levels of movement and comfort for itinerants , improvement the level of traffic safety , Reduce energy consumption and reduce environmental impacts improve productivity for organizations and individuals ). ) as well as identify the problems facing the transport system in the Iraq and the most important strategies proposed for the application of smart transport,on the sample in the Iraqi organizations ( university of the AL-Furat AL-Awsat technical and Directorate of Babylon Traffic ) ( population study) , the study sample consisted of ( 64 ) individuals who have the ability to express their opinions in this field ( civil Engineering , Electronic Engineering or Electricity , computer , communication ) , where a questionnaire was developed to collect the needed data to measure the variables of study . For testing hypothesis used descriptive statistics and simple regression and reached that there is an impact of intelligent transportation system of the public transport and comfort for itinerant sand improve productivity for organizations and individuals ) , which has no effect in the dimensions ( improvement the level of traffic safety , reduce energy consumption). The study recommended that the Iraqi government must develop a structural Map of the intelligent Transportation system in Iraq to development specifications and methods as a strategic framework through which the activities of the various parties involved can be integrated and unified policies within it , as well as taking priority and importance in the application of intelligent transport according to an approved strategy and the operation of empirical projects focusing on techniques where the risk is low